ФОРМУВАННЯ НАВИЧКИ ДО САМОСТІЙНИХ ЗАНЯТЬ ФІЗИЧНИМИ ВПРАВАМИ У СТУДЕНТІВ ПЕДАГОГІЧНОГО УНІВЕРСИТЕТУ (Педагогіка вищої та середньої школи, 2010)
The research reveals the fact that the majority of students positioning themselves as healthy people have skills of independent training in physical exercises. Most of such students have grown up in the families where parents didn't take part in physical activities.